Gathering Souls: Jesuit Missions and Missionaries in Oceania (1668-1945) Brill's Research Perspectives in Jesuit Studies - Coello de la Rosa, Alexandre (Brill Research Perspectives in Humanities and Social Sciences, 2019)
This essay deals with the missionary work of the Society of Jesus in today's Micronesia from the seventeenth to the twentieth century. In order to understand the Jesuits' evangelization project of gathering souls in the Oceanic archipelagos, it is important to place them into the broader context of Philippine politics.; Readership: All interested in the Jesuit evangelization of the Oceanic islands, and particularly in the history of the Mariana Islands and the Carolines from the seventeenth to the twentieth century.